Mitigation techniques for voltage SAG in power distribution systems by using dynamic voltage restorer (DVR): article / Muhammad Salman Sahak - Sahak, Muhammad Salman (Universiti Teknologi MARA (UiTM), 2010)
This paper describes the mitigation techniques for voltage sags in tbe distribution system. The Dynamic Voltage Restorer (DVR) is the proposed method used to compare the effective scheme control methods to mitigate the sags problem. Simulation results carried out by Matlabl/Simulink verify tile performance of the proposed method.